A Temporal Perspective on the Paradox of Pinocchio’s Nose - Gams, Matjaz; Černčič, Eva; Montanari, Angelo (Informatica, 2016)
The Paradox of Pinocchio's Nose was first proposed on February 2001 by 11-year-old Veronique Eldridge-Smith, the daughter of Peter Eldridge-Smith, who wrote an article in the journal Analysis. It was often proclaimed to be another version of the liar paradox, but this paper finds the paradox valid. However, as with most logic paradoxes when faced with real life and AI solutions, the paradox turns out valid for only a short period of time.